1991
DOI: 10.1073/pnas.88.8.3243
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution of the dystrophin-related gene product and expression in the mdx and dy mouse.

Abstract: We have previously reported a dystrophinrelated locus (DMDL for Duchenne muscular dystrophy-like) on human chromosome 6 that maps close to the dy mutation on mouse chromosome 10. Here we show that this gene is expressed in a wide range of tissues at varying levels. The transcript is particularly abundant in several human fetal tissues, including heart, placenta, and intestine. Studies with antisera raised against a DMDL fusion protein identify a 400,000 Mr protein in all mouse tissues tested, including those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(63 citation statements)
references
References 30 publications
5
57
0
1
Order By: Relevance
“…Several studies have already shown that utrophin is present near BMs in many tissues, 64 -67 including the kidney. 20 In the present study we found staining for utrophin in some but not all of the podocyte foot processes. That not all foot processes were positive could be due to low affinity of the mAb (DRP-2), because staining in IF was weak as well (see Figure 2D).…”
Section: Discussionsupporting
confidence: 56%
“…Several studies have already shown that utrophin is present near BMs in many tissues, 64 -67 including the kidney. 20 In the present study we found staining for utrophin in some but not all of the podocyte foot processes. That not all foot processes were positive could be due to low affinity of the mAb (DRP-2), because staining in IF was weak as well (see Figure 2D).…”
Section: Discussionsupporting
confidence: 56%
“…Taken together, our observation support the proposal that the recruitment of utrophin and other DAPC components to the membrane is the mechanism by which rhBGN counters dystrophic pathology in mdx mice. It is of particular note that total utrophin protein levels are up-regulated in DMD muscle (37)(38)(39). Therefore rhBGN can be expected to be effective in DMD patients.…”
Section: Discussionmentioning
confidence: 99%
“…This view is supported by the high level of sequence homology between utrophin and dystrophin in the carboxyl terminal region, which is involved in dystroglycan binding (Tinsley et al, 1992;Suzuki et al 1992), and by the observation that in dystrophin-deficient large calibre skeletal muscle dystroglycan is retained only at the neuromuscular junction (Matsumura et al, 1992), a site where utrophin is abundantly expressed . While little is known of the tissue distribution of dystroglycan in development and whether it colocalizes with utrophin, it is clear that both dystroglycan and utrophin show a wider distribution in adult tissues than dystrophin, for example both are abundant in some non-muscle sites such as lung and kidney (Love et al, 1991;Ibraghimov-Beskrovnaya et al, 1993). Very recently we described a short transcript of utrophin, which is the structural homologue of Dp 116 (apo-dystrophin-21, and is expressed exclusively in sensory ganglia and brain.…”
Section: Introductionmentioning
confidence: 99%